An Method to Quantify Control Rod Worth Uncertainty Propagated from Nuclear Data. (September 2017) - Hao, Chen; Hu, Wenqi; Zhao, Qiang; Li, Fu; Yu, Yan; Wang, Yizhen
Abstract: One of the main issues of nuclear reactor design is the accurate calculation of control rod worth. However, in the calculation results there exists uncertainty inevitably, which is propagated from uncertainty in input parameters, computing models and calculation methods. Therefore, carrying out control rod worth uncertainty quantification is urgent but full of challenges, especially for application of a feasible method for propagating input uncertainties to control rod worth. In this paper, a new uncertainty analysis method for quantifying uncertainty of control rod worth propagated from macroscopic cross sections has been proposed. The basic idea is to use efficient sampling method to propagate nuclear data uncertainties through the function between control rod worth and all macroscopic cross sections. This is done by applying perturbation theory. Numerical results indicate that the new method proposed in this paper is an effective way to quantify uncertainty of control rod worth propagated from nuclear data.